Design and Fabrication of the Portable Cultural Relic Display Cabinet for Public Exhibition - Sun, Bo; Ma, Quanjin; Na, Jian; Mat Rejab, Mohd Ruzaimi; Chong, ChinSeik; Fan, Weigang; Tang, Senyao; Wei, Jianxing (Journal of Advanced Research in Applied Mechanics, 2020)
It is known that cultural relics represent the art and aesthetic aspects of ancient history and provides high economic value in the auction market. Cultural relics have many different types, such as jade, porcelain and bronze ware, which are fragile and corrosive but expensive and unique. However, there are two common external conditions do harm to the valuable cultural relic, including humid (e.g. water or flood), high-temperature (e.g. fire) and impact vibration (e.g. earthquake or stealing). Therefore, this paper aims to design and fabricate the portable cultural relic display cabinet, which used to protect the fragile chinaware from irreversibly damaged conditions. The protective method is adopted the lifting system to drop to the display cabinet box under the above conditions. Two damaged conditions have been considered and detected the external conditions, which refers to flame and vibration sensor modules. It was concluded that this device had fast and valid response performance, and the results of experiment reveals it takes approximately 9.8 s-10.0 s to fully lower the porcelain into the main protective body on fire and vibration, such intense conditions. Based on its distinct characteristics above, this device can be widely used in the national museum, the private museum, artwork exhibition, etc.